Letter: reproducible evidence shows that exclusive enteral nutrition significantly reduces faecal calprotectin concentrations in children with active Crohn's disease—Authors' reply. Issue 11 (3rd November 2017) - Feathers, A.; Swaminath, A.; Ananthakrishnan, A. N.; Falzon, L.; Li Ferry, S.
Abstract : Linked Content This article is linked to Swaminath et al and Logan et al papers. To view these articles visithttps://doi.org/10.1111/apt.14253 andhttps://doi.org/10.1111/apt.14351 .